Senam Sehat Gembira pada Anak Prasekolah TK Wadifatimah Cirebon - Putri Nurfitriani; Mimin Sumiati; Tasya Amelia; Nazwa Niyatujahro; Hilda Anggreni; Muhammad Asyrofi; Tri Oktovian (Compromise Journal Community Proffesional Service Journal, 2025)
Happy and healthy gymnastics is a physical activity designed to enhance preschool children's gross motor skills through enjoyable and educational movements. This study was conducted at TK Wadifatimah Kota Cirebon to analyze the effectiveness of the program in improving movement coordination, balance, and rhythm-following skills in children aged 4-6 years. The method used was Participatory Action Research (PAR) with an Asset-Based Community Development (ABCD) approach, involving teachers, parents, and children in all stages of the program, from planning and implementation to evaluation. The program was implemented over 12 weeks with a sequence of warm-up, core, and cool-down movements. The results showed a significant improvement in children's gross motor skills. Movement coordination increased by 32.9%, balance by 28.5%, and rhythm-following skills by 33.8%. Additionally, the program encouraged greater participation in physical activities at home and created an enjoyable learning experience. Program evaluation indicated that active teacher involvement and the use of music as movement stimulation played a crucial role in enhancing the effectiveness of gymnastics. The study concludes that happy and healthy gymnastics can be an effective method for developing preschool children's gross motor skills. For optimization and sustainability, it is recommended that this activity be integrated into the school curriculum, with a wider variety of movements and more intensive parental involvement.